Access to syringes for HIV prevention for injection drug users in St. Petersburg, Russia: syringe purchase test study. - Fedorova, Ekaterina V; Skochilov, Roman V; Heimer, Robert; Case, Patricia; Beletsky, Leo; Grau, Lauretta E; Kozlov, Andrey P; Shaboltas, Alla V (BMC public health, 2013)
The HIV epidemic in Russia is concentrated among injection drug users (IDUs). This is especially true for St. Petersburg where high HIV incidence persists among the city's estimated 80,000 IDUs. Although sterile syringes are legally available, access for IDUs may be hampered. To explore the feasibility of using pharmacies to expand syringe access and provide other prevention services to IDUs, we investigated the current access to sterile syringes at the pharmacies and the correlation between pharmacy density and HIV prevalence in St. Petersburg.
Keywords: Adult; Cohort Studies; Commerce; Female; Health Knowledge, Attitudes, Practice; Health Services Accessibility; HIV Infections; Humans; Male; Pharmacies; Pharmacists; Professional Practice Location; Qualitative Research; Questionnaires; Russia; Substance Abuse, Intravenous; Syringes